KAJIAN HUKUM TINDAK PIDANA PENCURIAN YANG DILAKUKAN SECARA BERSAMA-SAMA - Nurjaman, Ari; Qomarudin , Heri (Journal Evidence Of Law, 2023)
The crime of theft which is committed jointly or often called theft with weighting, is a serious violation of law and has important implications in the criminal justice system. This study aims to examine the legal aspects related to the criminal act of theft which was carried out jointly based on the Criminal Code. The type of research used in this research is normative legal research. The legal material used is the Criminal Code as the primary legal material. The approach used is the statutory approach, the conceptual approach and the case approach, in this case the Case Study of Curanmor by Mother-in-law and Son-in-law in the Legal Area Tangerang Banten Police. The results of this study indicate that criminal responsibility for the perpetrators of the crime of theft committed jointly by in-laws and sons-in-law can be subject to Article 363 paragraph (1) with a maximum prison sentence of 7 (seven) years, can even increase to 9 (nine) years if in the trial process it is found that the theft was carried out at night by destroying the victim's house in order to facilitate the illegal possession of the target object. As for law enforcement for the perpetrators of the crime of theft through 2 stages, namely the pre-trial stage, namely investigation and investigation by the police and the trial stage, namely the process of proof and prosecution by the Public Prosecutor in the trial and the Verdict by the Panel of Judges. In relation to the case studies in this study, several factors lead to the occurrence of theft, including the high economic value of vehicles, relatively low vehicle safety, black markets, lack of public safety awareness, and social and economic disturbances. It is understood that the crime of motor vehicle theft is committed by the lower middle class in an effort to maintain life as an effort made by son-in-law and mother-in-law in this case;